PENINGKATAN HASIL BELAJAR MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERINTEGRASI NILAI BUDAYA ABBULO SIBATANG PADA PEMBELAJARAN ILMU PENGETAHUAN SOSIAL (IPS) SISWA KELAS V DI SDN NO. 6 BILACADDI KABUPATEN TAKALAR - Meisya Adriani, Dhea; Kaharuddin; Yanty Muchtar, Fitry (STKIP Subang, 2026)
Dhea Meisya Adriani, 2026. Improving Learning Outcomes through a ProblemBased Learning Model Integrated with the Cultural Values of A’bulo Sibatang in Social Studies Learning for Fifth Grade Students at SDN No. 6 Bilacaddi, Takalar Regency. Undergraduate Thesis. Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Universitas Muhammadiyah Makassar.Supervisor I: Kaharuddin Supervisor II: Fitri Yanty Muchtar This study aims to improve the Social Studies (IPS) learning outcomes of fifth-grade students through the implementation of a Problem-Based Learning (PBL) model integrated with the local cultural values of A’bulo Sibatang at SDN No. 6 Bilacaddi, Takalar Regency. The background of this research is based on the low learning outcomes of students in Social Studies, which are caused by the use of conventional teaching models, limited active student involvement, and the lack of optimal integration of local cultural values in the learning process. This research employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, conducted in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. The research subjects were 13 fifth-grade students. Data were collected through observation, learning outcome tests, and social attitude questionnaires. The data were analyzed using both quantitative and qualitative methods. The results of the study indicate that the implementation of the Problem-Based Learning model integrated with the local cultural values of A’bulo Sibatang significantly improved students’ Social Studies learning outcomes. The percentage of students achieving learning mastery increased from Cycle I to Cycle II and met the predetermined indicators of success. In addition, the application of this model had a positive impact on improving students’ social attitudes, such as cooperation, responsibility, and respect for local culture. Therefore, it can be concluded that the Problem-Based Learning model integrated with the local cultural values of A’bulo Sibatang is effective in improving Social Studies learning outcomes of fifthgrade students at SDN No. 6 Bilacaddi, Takalar Regency.